EFFICACY OF SHORT TERM CORTECOSTEROID THERAPY IN PATIENTS UNDERGOING MAXILLOFACIAL SURGERY. A SYSTEMATIC SCIENTIFIC REVIEW. - Suhael Ahmed, Sami Ali Al Qahishi, Sultan Ghazi Ahmad Alsulaimani, Ahmed Abdu Sulaiman Bajafar, Samar Jamil Hamza Fadul, Saeedah Abdu Sulaiman Bajafar, Ahmad Waleed Mohammed Ali Malas, Naeimah Ahmed Alsumali, Abdulrhman Aldawsari (Chelonian Research Foundation, 2023)
Glucocorticoids, also known as corticosteroids or steroids, are drugs derived from cholesterol. They are synthesized by the adrenal cortex, along with other hormones, such as cortisol and aldosterone. Glucocorticoid drugs are recommended for patients undergoing surgery in maxillofacial region due to their high efficacy against inflammatory and immune processes. However, these drugs are restricted due to their multiple and serious adverse effects. The objective of this study was to verify the efficacy of short term corticosteroids administered in maxillofacial surgeries, based on the characteristics of the patient so as to select the best therapeutic strategy. Articles in the databases such as PubMed, Medline, Cochrane Library, Scopus and Web of science were searched using keywords. A total of 27 articles were selected to address the proposed objectives. The results obtained show that it is effective and safe to use glucocorticoids on short term basis as pre or postsurgical therapy in maxillofacial surgery to control the processes of inflammation, pain, and edema. Keywords – corticosteroids, anti-inflammatory, postoperative, maxillofacial surgery, dexamethasone, methylprednisolone